2019
DOI: 10.1002/rcr2.411
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulmonary vasodilators on pulmonary hypertension associated with POEMS syndrome

Abstract: Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome is a rare plasma cell disease. Patients with POEMS syndrome are considered to be at a high risk of developing pulmonary hypertension (PH). We report a 51‐year‐old woman diagnosed with PH associated with POEMS syndrome. She was started on dexamethasone and thalidomide. Although, the plasma vascular endothelial growth factor (VEGF) level decreased, systolic pulmonary artery pressure (sPAP) remained high. Auto‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Besides, it's been reported that thalidomide can reduce the expression of IL-18 and TNF-α in the alveolar lavage fluid in patients with IPF (41). It can be seen that thalidomide potential provides a good antipulmonary fibrosis effect (42,43). However, the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it's been reported that thalidomide can reduce the expression of IL-18 and TNF-α in the alveolar lavage fluid in patients with IPF (41). It can be seen that thalidomide potential provides a good antipulmonary fibrosis effect (42,43). However, the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%